The conflicts of 2020 : reflections from a graduate course on diversity and social justice in higher education - Brigham, Alyssa; Stanley, Christine A. (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
The year 2020 presented conflicts in higher education, including a global pandemic, racial protests, cries for Black Lives Matter following the deaths of Black women and men by police, education moved online to virtual classrooms, and the U.S. economy struggling as millions of Americans were furloughed or worked remotely and ordered everything curbside; all of this compounded by an election year. This book is a compilation of perspectives shared from students enrolled in a graduate course on diversity and social justice in higher education who found community in sharing their personal and professional experiences associated with identity and allyship development, socialization, activism, institutionalized racism, academic traditions, advising, to implications for change in higher education policies, processes, and practice.
Keywords: Education, Higher -- Social aspects -- United States.; Social justice and education -- United States.; United States -- Social conditions -- 21st century.; Education -- Philosophy, Theory & Social Aspects.; Ethnic studies.; Philosophy and theory of education.; elektronické knihy; electronic books